Towards effective outbreak detection: a qualitative study to identify factors affecting nurses' early warning surveillance practice in Solomon Islands - Adam T. Craig; Cynthia A. Joshua; Alison R. Sio; Michael Lauri; John Kaldor; Alexander E. Rosewell; Gill Schierhout (BMC, 2018)
Abstract Background Intelligence generated by a surveillance system is dependent on the quality of data that are collected. We investigated the knowledge, attitudes and practices of nurses responsible for outbreak early warning surveillance data collection in Solomon Islands to identify factors that influence their ability to perform surveillance-related tasks with rigour. Methods We interviewed 12 purposively selected surveillance nurses and conducted inductive analysis on resulting data. Results Interviewees were knowledgeable and willing to contribute to the surveillance system. Constraining factors included the perception that surveillance was less important than patient care and could be 'deferred' during busy periods and wide variability in the application of case definitions. Motivating factors were frequent in-clinic training, formal recognition for good performance, incentives and designation of a focal point. Nurses held mixed views about the effect of mobile technologies on surveillance practice. Conclusions This study identified several challenges to consistent and accurate data collection and reporting. Engagement of different parts of the health system, including human resources and health facilities' management, is needed to address these challenges.